The Nrf2-HO-1 system and inflammaging - O’Rourke, Sinead A.; Shanley, Lianne C.; Dunne, Aisling (Frontiers in Immunology, 2024)
Nrf-2 is a master transcriptional regulator of a number of genes involved in the adaptive response to oxidative stress. Among the genes upregulated by Nrf2, heme oxygenase-1 (HO-1) has received significant attention, given that the products of HO-1-induced heme catabolism have well established antioxidant and anti-inflammatory properties. This is evidenced in numerous models of inflammatory and autoimmune disease whereby induction of HO-1 expression or administration of tolerable amounts of HO-1 reaction products can ameliorate disease symptoms. Unsurprisingly, Nrf2 and HO-1 are now considered viable drug targets for a number of conditions.In recent years, the term 'inflammaging' has been used to describe the low-grade chronic inflammation observed in aging/aged cells. Increased oxidative stress is also a key factor associated with aging and there is convincing evidence that Nrf2, not only declines with age, but that Nrf2 and HO-1 can reduce cellular senescence and the senescence-associated secretory phenotype (SASP) which is now considered an underlying driver of age-related inflammatory disease. In this review, we describe the role of oxidative stress in 'inflammaging' and highlight the potential anti-aging properties of the Nrf2-HO-1 system. We also highlight established and newly emerging Nrf2 activators and their therapeutic application in age related disease.